Study of Two Dimensional Materials by Scanning Probe Microscopy - Plumadore, Ryan (Université d'Ottawa / University of Ottawa, 2019)
This thesis explores structural and electronic properties of layered materials at the nanometre scale. Room temperature and low temperature ultrahigh vacuum scanning probe microscopy (scanning tunneling microscopy, scanning tunneling spectroscopy, atomic force microscopy) is used as the primary characterization method. The main findings in this thesis are: (a) observations of the atomic lattice and imaging local lattice defects of semiconducting ReS2 by scanning tunneling microscopy, (b) measurement of the electronic band gap of ReS2 by scanning tunneling spectroscopy, and (c) scanning tunneling microscopy study of 1T-TaS2 lattice and chemically functionalizing its defects with magnetic molecules.
Keywords: Scanning Tunneling Microscopy; 2D Materials; Transition Metal Dichalcogenide; TMDC; Rhenium Disulfide; Tantalum Disulfide